Brief Principles of Macroeconomics, 9th Edition - N. Gregory Mankiw (Cengage Learning, 2020)
Provide a concise, approachable introduction to macroeconomics that allows all types of learners to grasp economic concepts quickly and build a strong foundation. Part of the most widely-used learning solution in economics classrooms worldwide, Mankiw's BRIEF PRINCIPLES OF MACROECONOMICS, 9E covers only the most important principles to avoid overwhelming students with excessive detail. Extensive updates, relevant examples, and carefully crafted content written by leading economics author Gregory Mankiw work seamlessly with the latest powerful student-focused resources.